Teachers' Ontology-based Reasoning for Assessment in Student-centered Learning Environments. (2nd January 2023) - Bergner, Yoav; Chen, Ofer
ABSTRACT: We present an exploratory study on the use of ontologies for student assessment during a focus group with teachers in student-centred learning environments. The work is framed by a theoretical argument about coherence between instructional values and assessment systems, and how this may be achieved through a "community of judgment" with teachers at the centre. The purpose of the study was to understand the process and perceived usefulness of collaborative ontology development, at a narrative and conceptual level without grades or detailed probabilistic relationships. Findings of two kinds are discussed. First, we identified a set of framework-building moves used by teachers during ontology-based reasoning. Second, we present evidence that participants perceived the ontology development process to be useful and empowering in sharpening their ability to communicate nuanced assessment arguments.